Effects of perioperative parenteral nutrition on wound healing and hospital stay in surgical patients: a randomized controlled study - Ganaie, Abdul Rashid; Itoo, Mohd. Saleem; Bhat, Gh. Mohd. (International Journal of Research in Medical Sciences, 2017)
Background: The present randomized controlled study was carried out over a period of one year to observe the effects of perioperative parenteral nutrition on wound healing and hospital stay. Methods: Hundred patients, admitted in Department of surgery, Government Medical Srinagar were divided into two groups of 50 each. Group A (Study group) and group B (Control group). Group A patients were given perioperative parenteral nutritional support whereas patients in control group received no perioperatve parenteral nutritional support. Results: Complications like wound infections, sepsis, abscess formation, anastomotic leak and wound dehiscence were considerably less in the study group. The time period to resolve complications and overall hospital stay was also less in the study group. Conclusions: Parenteral perioperative nutritional support has a definite role in the management of selected surgical patients. It reduces the septic or non-septic complication and over all post-operative hospital stay. It should be included in the management of surgical patients if affordable.